Pottery from roman Malta - Anastasi, Maxine, 1986- (Archaeopress archaeology., 2019)
A comprehensive study of Maltese pottery forms from key stratified deposits spanning the 1st century BC to mid-4th century AD. Ceramic material is analysed and quantified in a bid to understand Maltese pottery production during the Roman period, and trace the type and volume of ceramic-borne goods that were circulating the central Mediterranean.